2016
DOI: 10.1007/s10565-016-9362-9
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization of mitochondrial membrane potential is the initial event in non-nucleoside reverse transcriptase inhibitor efavirenz induced cytotoxicity

Abstract: Efavirenz is a non-nucleoside reverse transcriptase inhibitor (NNRTI) and an active constituent of the highly active antiretroviral therapy regime. It has significantly contributed in control and management of human immunodeficiency virus propagation. However, EFV administration has also led to severe adverse effects, several reports highlighted the role of EFV in mitochondrial dysfunction and toxicity but the molecular mechanism has been poorly understood. In present study, human hepatoma cells Huh 7.5 were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 66 publications
2
39
0
Order By: Relevance
“…Treatment with EFV also resulted in about 50% reduction in mtDNA compared to treatment with DMSO. Although, EFV does not inhibit Pol-γ, we observed mtDNA depletion in CEM cells treated with 1xC max of EFV; this is consistent with previous report using human hepatoma cells Huh 7.5 (27). Thus, EFV has several affections on mitochondria.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Treatment with EFV also resulted in about 50% reduction in mtDNA compared to treatment with DMSO. Although, EFV does not inhibit Pol-γ, we observed mtDNA depletion in CEM cells treated with 1xC max of EFV; this is consistent with previous report using human hepatoma cells Huh 7.5 (27). Thus, EFV has several affections on mitochondria.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we sought to investigate whether combining EFV with TDF/FTC will moderate reported EFV-associated mitochondrial dysfunction (8, 18, 25-27) and perturbation of cholesterol biosynthesis (8, 28, 29). Most of the reported EFV-induced toxicities are from in vitro studies where cells were treated with EFV alone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations